What do 'humans' need? Sufficiency and pluralism - Davies, B (Taylor & Francis, 2024)
Sufficientarians face a problem of arbitrariness: why place a sufficiency threshold at any particular point? One response is to seek universal goods to justify a threshold. However, this faces difficulties (despite sincere efforts) by either being too low, or failing to accommodate individuals with significant cognitive disabilities. Some sufficientarians have appealed to individuals’ subjective evaluations of their lives. I build on this idea, considering another individualized threshold: ‘tolerability’. I respond to some traditional challenges to individualistic approaches to justice: ‘expensive’ tastes, and adaptive preferences. Finally, I end by offering some suggestions about how this relates to policymaking.